Efektifitas Forum Dilkumjakpol dalam Kerangka Integrated Criminal Justice System - Oki Wahju Budijanto (Badan Strategi Kebijakan Hukum, 2013)
Evaluation of the effectiveness of the forum court, Justice and Human Rights, Prosecution, and Police (Dil- kumjakpol) within the framework of the Integrated Criminal Justice System aims to determine how the effec- tiveness of the framework Dilkumjakpol forum Integrated Criminal Justice System and to determine the fac- tors that led to the difficulty of law enforcement in Indonesia in the framework realize the Integrated Criminal Justice System. While the benefits of this evaluation are expected as an ingredient in making recommendations relating to policy formulation Dilkumjakpol forum as well as reading materials to enrich the science and lit- erature. The method used is a qualitative approach. While data collection techniques used in this evaluation, which consists of in-depth interviews (in-depth interviews), questionnaires and document study as secondary data. Based on the evaluation results, it can be concluded that, (1) Dilkumjakpol forum yet effective, although there are variations among the five provinces., DIY considered more effective than other provinces in terms of coordination. (2) there are three factors that make it difficult for law enforcement in Indonesia in realizing the framework of the Integrated Criminal Justice System, namely management factors, institutional factors and factors with a variety of substances among the five provinces. Variations in question are contained in the terms of the management regarding the new budget budgeted in 2012, limited human resources, ego sectoral leadership and commitment of each agency. The same variation also occurs in the institutional factors and factors of substance.